Reflections on water in the hottest year (so far) - McCartney, Matthew P.; Uhlenbrook, Stefan; Matthews, John; Ravindranath, Darshini; Ringler, Claudia (CGIAR System Organization, 2024)
This CGIAR Initiative on NEXUS Gains webinar explored the critical interplay between climate change and water resources. It looked at the impacts of climate change on water cycles, examining shifts in precipitation patterns, increased evaporation, and the rising frequency of extreme events. It discussed why nexus approaches are central to technical and policy approaches for climate resilience and adaptation. Additionally, it provided an overview of key discussions on water and outcomes from the recently concluded UNFCCC COP29 and an overview of important water research for climate change mitigation and adaptation.